Visuelle modellbasierte Experimente in den (digitalen) Geisteswissenschaften - Zoe Schubert; Jan Wieners; Øyvind Eide (Zeitschrift für digitale Geisteswissenschaften)
This article presents a number of visual experiments with a special focus on processes of media transformation and modelling. In the selected examples, the development and use of computer systems are used to create different visual artefacts. These experiments can only be performed with the use of models in modelling processes. This chapter shows how important modelling and the use and development of software is for the analytical reflections and thus for the gaining of new knowledge. We also show how these points tend towards a more general pattern: visual experiments in the digital humanities cannot be performed without the use of models.